2021
DOI: 10.3233/jad-210163
|View full text |Cite
|
Sign up to set email alerts
|

Predicting and Characterizing Neurodegenerative Subtypes with Multimodal Neurocognitive Signatures of Social and Cognitive Processes

Abstract: Background: Social cognition is critically compromised across neurodegenerative diseases, including the behavioral variant frontotemporal dementia (bvFTD), Alzheimer’s disease (AD), and Parkinson’s disease (PD). However, no previous study has used social cognition and other cognitive tasks to predict diagnoses of these conditions, let alone reporting the brain correlates of prediction outcomes. Objective: We performed a diagnostic classification analysis using social cognition, cognitive screening (CS), and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 100 publications
0
25
0
Order By: Relevance
“…The validity and discriminative capacity of the IFS was studied in patients with bvFTD, AD, and healthy controls. The IFS differentiates patients with dementia from healthy controls ( 50 , 61 ) and patients with bvFTD from AD ( 50 ). Two studies, one in Argentina and the other in Peru, suggested that the IFS presented greater clinical utility in differentiating bvFTD from AD in comparison with the FAB ( 62 , 63 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The validity and discriminative capacity of the IFS was studied in patients with bvFTD, AD, and healthy controls. The IFS differentiates patients with dementia from healthy controls ( 50 , 61 ) and patients with bvFTD from AD ( 50 ). Two studies, one in Argentina and the other in Peru, suggested that the IFS presented greater clinical utility in differentiating bvFTD from AD in comparison with the FAB ( 62 , 63 ).…”
Section: Resultsmentioning
confidence: 99%
“…Currently, social cognition is primarily assessed with the Mini-SEA. Although there are promising results on the diagnostic utility of the Mini-SEA for the differential diagnosis of bvFTD of PD and AD ( 61 , 198 ), social cognition assessment still faces essential limitations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The resulting functional connectivity (FC) correlation coe cients between all pairs of regions (AAL atlas) were used to perform Spearman's correlations with the scores of each predictor: loneliness (UCLA score), and social network (LSNS-R score). Following procedures from recent research [50][51][52] signi cance thresholding of neuroimaging results was set to p ≤ .001 (uncorrected). Uncorrected statistical threshold has been used previously to avoid the detrimental effects of liberal primary thresholds on false positives (especially in modest sample sizes such as ours) [53][54][55] .…”
Section: Functional Connectivity Analysesmentioning
confidence: 99%